High Visual-Spatial Intelligence Students’ Creativity in Solving PISA Problems - Triutami, Tabita Wahyu; Hariyanti, Uun; Novitasari, Dwi; Tyaningsih, Ratna Yulis; Junaidi, Junaidi (Universitas Muhammadiyah Mataram, 2021)
Creativity is very necessary for learning mathematics, especially when solving geometry problems. This research aims to describe 4th year mathematics education students’ creativity in solving geometry problems. Creativity in this research is focused on fluency, flexibility, and originality of student anwer when solving geometry problems. This research is an explorative descriptive research through a qualitative approach. The participants were 7 fourth year mathematics education students of state University in Mataram, who have a high level of visual-spatial intelligence. The data was collected by written test and interview. The test consisted of two open-ended geometry problems about transforming 3-dimensional images into 2-dimensional images and making 2-dimensional images with a predetermined circumference. The problems are modification of the 2006 PISA test. The result showed that subjects with high visual-spatial intelligence levels met all indicators of creativity. In solving problems that meet the aspects of fluency, flexibility and originality, they combine mental rotation and mental visualization abilities and include using their visual experience by modifying the information obtained and the initial problem solving ideas obtained. This also enables them to produce original problem solutions. The results of this research can be used as an illustration and a guideline to assess students’ creativity with high visual-spatial intelligence level.